Recent antitumor therapy does not increase Omicron COVID-19 severity in cancer patients: a two-center retrospective study in China - Liu, Ying; Zhu, Wenyao; Wang, Zhiwu; Yu, Jiarui; Dong, Liang; Li, Chunyang; Wang, Wei; Zhang, Fuhui; Ding, Shuanghui; Sun, Lu; Yang, Zhao; Zhang, Chao; et al. (Frontiers in Oncology, 2023)
The impact of anticancer therapy and related clinical factors on the severity of COVID-19 in cancer patients during the Omicron pandemic has not been established.The recent outbreak in China caused predominantly by the BA.5.2 and BF.7 strains of Omicron provided us with the opportunity to observe objectively the impact of this strain in oncology patients. We initiated this two-center retrospective study in China to determine the impact of anti-cancer treatment, other clinical factors, and cancer characteristics on COVID-19 severity in cancer patients infected with coronavirus during the SARS-CoV-2 Omicron variant pandemic in China.We retrospectively included 554 cancer patients infected with COVID-19 from two medical centers. Data on their anticancer treatment prior to COVID-19 infection and general clinical characteristics (sex, age, past medical history, etc.) were collected.Univariate statistical analysis was performed to identify the factors associated with the severity of COVID-19.Among 554 cancer patients infected with COVID-19, there were 15 (2.7%) severe/critical cases, 86 (15.5%) cases with medium severity, and 453 (81.8%) cases with mild severity. Univariate analysis revealed that advanced age, male sex, worse ECOG score, unvaccinated status, and previous liver, kidney, and brain diseases were associated with more severe COVID-19. However, recent antitumor therapy, including cytotoxic chemotherapy within two weeks did not have a significant correlation with the severity of COVID-19 caused by the Omicron variant.The severity of COVID-19 caused by the Omicron variant is not exacerbated by recent anticancer therapy in cancer patients. Therefore, anticancer therapy should not be discontinued in such cases, especially those with mild severity.